Elateridae (Coleoptera) of Lebanon - Németh, Tamás (Zootaxa, 2019)
A checklist of Elateridae of Lebanon is provided. Altogether, 54 species classified in 23 genera are listed, with 11 species reported from the country for the first time. Elathous agilis sp. nov. and Megathous tannourinensis sp. nov. are described, compared with congeners, and their main diagnostic characters are figured.